The progenitor of SN 1987A - Podsiadlowski, P; Morris, T; Ivanova, N (2007)
The nature of the progenitor has been one of the major mysteries of SN 1987A. It has long been suspected that the various anomalies of the supernova, the blue color of the progenitor, the chemical anomalies in the envelope and the triple-ring nebula surrounding it, could be the direct consequence of the merger of two massive stars some 20,000yr before the explosion. Here we present the results of detailed recent numerical simulations of such mergers and show that these can indeed explain all of the main anomalies. In particular, we present detailed 3-dimensional hydrodynamical simulations that show how the triple-ring nebula is likely to have formed, providing the best evidence for a binary merger to date. We also discuss how a merger may naturally explain other structures in the nebula, further strengthening the model and providing future observational tests.